P04.09 MicroRNA analysis of the invasive margin of Glioblastoma reveals druggable therapeutic targets in lipid metabolism pathways. (19th September 2018) - Alfardus, H; de los Angeles Estevez Cebrero, M; Rawlinson, J; Lourdusamy, A; Grundy, R; McIntyre, A; Smith, S
Abstract: Background: Heterogeneity of gene expression in Glioblastoma (GBM) has been recently recognised as a key feature involved in therapy resistance with invasive cells remaining after surgery and displaying unique molecular features. The dysregulation of small non-coding RNAs known as microRNAs (miRNAs) can disrupt gene regulatory networks and contribute to GBM development. However, the intra-tumour heterogeneity of miRNA expression in GBM has not yet been investigated. Material and Methods: Global miRNA expression profiling was performed in 45 GBM surgical specimens sampled from the tumour necrotic core, proliferative rim and the invasive margin. Gain-of-function studies were conducted using transfection of selected mature miRNAs into GBM cell lines. Global metabolomic profiling by liquid chromatography coupled with electrospray mass spectrometry (LC-ESI-MS) and gene expression assays were used to identify molecular targets regulated by miRNAs in GBM cells. Transwell assays were performed to examine the migration and invasion effects of inhibiting targets expression. Evaluation of targets expression in tumour tissue samples was performed by qRT-PCR, flow cytometry and immunohistochemical analysis. Results: We identified two significantly upregulated miRNAs in the invasive margin compared to the core and the rim of the tumour. Integrated metabolomic and gene expression analysis revealed that these miRNAs may act synergistically to target key enzymes involved in fatty acid oxidation (ACOX1 and CPT2) and lipoprotein uptake and secretion (LDLR). ACOX1, CPT2 and LDLR were found to be expressed at lower levels in the core and the rim relative to the invasive edge samples. The pharmacological inhibition of CPT2 and LDLR resulted in a significant reduction in GBM cell invasion. Conclusion: Our finding indicates that lipid metabolism may present a possible vulnerability of GBM invasive margin. Understanding the function of miRNAs in regulating lipid homeostasis in GBM may provide novel avenues for GBM therapy.